UPAYA MEMINIMALISIR KECANDUAN GADGET PADA SISWA MELALUI PENERAPAN PROGRAM LAYANAN BIMBINGAN KLASIKAL DI SMA NEGERI 2 PAMEKASAN - Zahrah, Murniatuz; Enisatul Risqina; Waqiatul Masrurah (Jurnal Pendidikan Nusantara, 2025)
This study aims to minimize gadget addiction in eleventh-grade students through the implementation of a classical guidance service program at Pamekasan 2 State Senior High School. Classical guidance services are a program that provides information and orientation that is beneficial for students face-to-face and scheduled between the guidance and counseling (BK) teacher and all students in the class. Students are provided with classical guidance services by the BK teacher with the hope that they can understand the negative impacts of gadgets, so that students can better manage their time and be wiser in using gadgets properly. The subjects of the study were eleventh-grade students of Pamekasan 2 State Senior High School. The research method used was a qualitative approach with data collection techniques through observation, instruments, and documentation. The results of this study indicate that gadget addiction in students can disrupt learning concentration, reduce social interaction, and trigger unproductive behavior. Through interactive and structured classical guidance services, students begin to understand the negative impacts of excessive gadget use and demonstrate behavioral changes by reducing the frequency of gadget use outside of learning needs. This service also encourages students to use gadgets wisely and prioritize academic and social activities. The results of the study showed that by using classical guidance services, the negative impact of gadgets on teaching and learning activities was reduced. In conclusion, the classical guidance program is effective in reducing gadget addiction.